From Adoption to Continuance: Understanding Self-Efficacy’s Role in TVET Digital Learning - Ismail, Mohd Hafizul; Shaikh Ali, Siti Haryani; Husin, Husna Sarirah; Hassan, Sallaudin; Mohd Ali, Siti Nur Dina (Journal of Technical Education and Training, 2025)
This study explores how lecturers' self-efficacy affects their satisfaction and willingness to continue using digital technologies (DT) in Technical and Vocational Education and Training (TVET) teaching and learning (T&L). A survey was conducted with 150 lecturers from the Malaysian TVET Higher Learning Institution. It aimed to assess how self-efficacy influences both satisfaction and the continuance use of DT in TVET education. The study employed a quantitative research design, with structured questionnaires measuring self-efficacy, satisfaction, and continuance intention. Using the Structural Equation Model (SEM) analysis, the results showed that self-efficacy has a strong and significant positive impact on both satisfaction and continuance use of DT in TVET settings. Lecturers with higher self-efficacy were more satisfied with technology use, which strengthened their commitment to ongoing adoption. The findings also indicated that satisfaction partially mediated the relationship between self-efficacy and continuance intention. This indicates that while self-efficacy directly supports long-term technology use, satisfaction further enhances the continued use of DT in TVET T&L.